Nano-Enabled Strategies for Soil Fertility and Plant Productivity: A Sustainable Approach - Akbar, Asiya; Aqsa Yaqoob,; Fatima Asif,; Muhammad Waqar,; Misbah Rani,; Qurat Ul Ain Hyder,; Hafiz Muhammad Usman, (Dialogue Social Science Review (DSSR), 2025)
Nanotechnology has recently emerged as another innovative technology that concerns agriculture. It brings solutions to plant growth, soil fertility, and crop yield. Current studies are aimed at assessing the effects of zinc oxide (ZnO) and titanium dioxide (TiO₂) nanoparticles on seed germination, plant growth, biochemical response, and soil microbial activities. Plants were subjected to various concentrations of nanoparticles, and the impacts on the rest of the physiological-biochemical parameters were determined. Hence, it was revealed that seed germination percentage increased chlorophyll content and biomass production, though the differences in ZnO and TiO nanoparticles were significant. The roots were more extensive, and nutrient uptake also was increased because the nanoparticles control the action of auxins and enhance nutrients in the soil. The high antioxidant enzyme activity in biochemical analyses also resulted in reduced oxidative damage and increased resistance of the plant-soil analyses indicating that nitrogen and phosphorus availability was enhanced with a concomitant positive effect on microbial communities at optimal levels of nanoparticles. However, phytotoxic effects were noted at higher concentrations, emphasizing the need for dose optimization. Indeed, statistical analysis validated the finding and indicated that these nanoparticles hold great promise for application as green inputs in agriculture. More studies need to be carried out in the long term on environmental implications and develop safe means of application for large-scale agricultural use since, in this study, ZnO and TiO₂ nanoparticles seem to have a positive influence on plant growth and soil enhancement.